Economic valuation of ecosystem goods and services: a review for decision makers. Issue 4 (2nd October 2019) - Tinch, Robert; Beaumont, Nicola; Sunderland, Tim; Ozdemiroglu, Ece; Barton, David; Bowe, Colm; Börger, Tobias; Burgess, Paul; Cooper, Canon Nigel; Faccioli, Michela; Failler, Pierre; Gkolemi, Ioanna; et al.
ABSTRACT: There is increasing interest in the use of economic valuation of ecosystem goods and services for a wide variety of purposes. These include relatively familiar uses in project appraisal and more novel applications in advocacy, performance tracking and accounting in public and private settings. Decision makers who use valuation information need to understand the background, strengths and weaknesses of these approaches. The methods have a strong foundation in economic theory and offer a rapidly growing evidence base, improving ability to evaluate a broad range of ecosystem goods and services. Nevertheless, there are theoretical and practical limitations that need to be understood and kept in mind when interpreting results. In this paper, we briefly review the economic valuation methods and situate them in their historical and theoretical contexts. We assess the main critiques, attempts at resolving them, and implications for the usefulness of the methods in different contexts. We examine the main barriers and opportunities for wider uses of valuation evidence, and draw conclusions on the appropriate role of valuation in future, as a tool for aiding reflection and deliberation processes.